Molecular identification of adenovirus causing respiratory tract infection in pediatric patients at the University of Malaya Medical Center - Juraina, Abd-Jamil; Boon-Teong, T.; Eddy, H.; Nuruliza, R.; Sazaly, A.B. (2010)
Background There are at least 51 adenovirus serotypes (AdV) known to cause human infections. The prevalence of the different human AdV (HAdV) serotypes varies among different regions. Presently, there are no reports of the prevalent HAdV types found in Malaysia. The present study was undertaken to identify the HAdV types associated primarily with respiratory tract infections (RTI) of young children in Malaysia.